Plating/Stripping Behavior of Actual Lithium Metal Anode - Liu, He; Cheng, Xin‐Bing; Xu, Rui; Zhang, Xue‐Qiang; Yan, Chong; Huang, Jia‐Qi; Zhang, Qiang (Advanced energy materials, 2019)
Lithium (Li) metal anodes exhibits the potential to enable rechargeable Li batteries with a high energy density. However, the irreversible plating and stripping behaviors of Li metal anodes with high reactivity and dendrite growth when matching different cathodes in working cells are not fully understood yet. Herein the working manner of very thin Li metal anodes (50 µm, 10 mAh cm−2) is probed with different sequences of Li plating and stripping at 3.0 mA cm−2 and 3.0 mAh cm−2. Dendrite growth and dead Li forms on the surface of the initially plated Li electrode (P‐Li), while Li dendrites form in the pit of the initially stripped Li electrode (S‐Li). This induces the differences in reactive sites, distribution of dead Li, and voltage polarization of Li metal anodes. There is a gap of 15–20 and 13–16 mV for the end voltages between S‐Li and P‐Li during stripping and plating, respectively. When matching LiFePO4 and FePO4 cathodes, P‐Li | LiFePO4 cells exhibit a 30‐cycle longer lifespan with smaller end polarization due to differences in the sequences of Li plating and stripping. This contribution affords emerging working principles for actual Li metal anodes when matching lithium‐containing and lithium‐free cathodes. The working manner of Li metal anodes are probed with different sequences of Li plating and stripping at 3.0 mA cm−2 and 3.0 mAh cm−2. There are differences in reactive sites, distribution of dead Li, and voltage polarization. This contribution affords the emerging working principles of Li metal anodes with matching lithium‐containing and lithium‐free cathodes.